Decreased spasticity of Baishaoluoshi Decoction through the BDNF/TrKB-KCC2 pathway on poststroke spasticity rats. Issue 14 (6th October 2021) - Xie, Le; Xie, Yao; Mao, Guo; Cao, Sijia; Fang, Rui; Zhou, Shen; Jiang, Junlin; Yao, Ting; Fan, Jianhu; Liu, Dong; Wu, Dahua; Ge, Jinwen
Abstract : Objective: K + –Cl − cotransporter-2 (KCC2), which primarily extrudes chloride in mature neurons, triggers hemiplegia limb spasticity after ischemic stroke by affecting neuronal excitability. Our previous study revealed that the Chinese herb Baishaoluoshi Decoction decreases hemiplegia limb spasticity in poststroke spasticity (PSS) patients. This study aimed at elucidating on the effects of Baishaoluoshi Decoction on the BDNF/TrKB-KCC2 pathway in PSS rat models. Methods: Middle cerebral artery occlusion (MCAO) was adopted for the establishment of PSS rat models. Muscle tension was evaluated by Modified Ashworth Scale. Nissl staining and transmission electron microscopy were used to measure the protective effects of Baishaoluoshi Decoction on ischemic injury-induced neuronal damage due to MCAO. Expression levels of BDNF, TrKB, and KCC2 in brain tissues around the infarct and brainstem were detected by immunohistochemical staining. Results: It was found that Baishaoluoshi Decoction suppressed hemiplegia limb spasticity and alleviated the damage in neurons and synapses in PSS rat models. Importantly, the expression of BDNF, TrKB, and KCC2 in brain tissues around the infarct and brainstem were significantly upregulated after treatment with low-dose and high-dose Baishaoluoshi Decoction. Conclusion: Suppression of spasticity by Baishaoluoshi Decoction in PSS rat models may be correlated with upregulated BDNF/TrKB-KCC2 pathway, which may be a complementary therapeutic strategy for PSS.